If f(x) = x + 3

4x – 5

, g(x) = 3 + 5x

4x – 1 then show that

(fog) (x) = x.​

Question

If f(x) = x + 3

4x – 5

, g(x) = 3 + 5x

4x – 1 then show that

(fog) (x) = x.​

in progress 0
Brielle 11 months 2021-07-05T03:43:39+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-07-05T03:45:08+00:00

    (tex) ғ(x)=(x+)/(x-)

    ɢ(x)=(+x)/(x-)

    ғ.ɢ(x)=ғ{ɢ(x)}

    =ғ{+x/x-}

    ={(+x)/(x-)+}/{(+x)/(x-)-}

    ={(+x+x-)/+x-x+}(/tex)

    0
    2021-07-05T03:45:13+00:00

    \huge \sf \bf {\boxed{\underline {\red{\underline {✠Aɴʂᴡᴇʀ࿐ :−}}}}}

    (tex) ғ(x)=(x+)/(x-)

    ɢ(x)=(+x)/(x-)

    ᴛʜᴇɴ,

    ғ.ɢ(x)=ғ{ɢ(x)}

    =ғ{+x/x-}

    ={(+x)/(x-)+}/{(+x)/(x-)-}

    ={(+x+x-)/+x-x+}(/tex)

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )